2017
DOI: 10.1039/c7nj00402h
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent closed shell nickel(ii) pyridyl-azo-oximates and the open shell anion radical congener: molecular and electronic structure, ligand redox behaviour and biological activity

Abstract: Luminescent nickel(ii) complexes have been synthesized using redox-active azo-oximes. The superior π-acidity of the organic backbone is a key to the isolation of Ni(ii) anion radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The sharp feature and small signal width (ΔH = 3.07 mT) of the spectrum without the presence of any hyperfine structures indicate that there is practically no contribution of the metal center to the spin-bearing orbital. [28][29][30][31]53 This is consistent with the radical anion description of 2 with the odd electron being virtually delocalized over the ligand framework. Furthermore, Mulliken spin-density calculations for 2a…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The sharp feature and small signal width (ΔH = 3.07 mT) of the spectrum without the presence of any hyperfine structures indicate that there is practically no contribution of the metal center to the spin-bearing orbital. [28][29][30][31]53 This is consistent with the radical anion description of 2 with the odd electron being virtually delocalized over the ligand framework. Furthermore, Mulliken spin-density calculations for 2a…”
supporting
confidence: 82%
“…It is worth mentioning that the coordinated N-N(azo) lengths acts as an indicator of the ligand valence for these types of redox non-innocent azo ligands. [24][25][26][27][28][29] In general, the N-N(azo) distance of the coordinated neutral azo-aromatic ligands falls in the range 1.28 ± 0.02 Å while the corresponding lengths in mono-reduced form lies within 1.33 ± 0.02 Å with an approximate increase of 0.05 Å. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The results clearly point toward the presence of an odd electron over the azo function of the ligand skeleton in complex 2a, and theoretical investigations disclose that the unpaired electron is practically delocalized over the azo-oxime framework (vide infra) with the highest contribution from the azo moiety (Fig.…”
Section: Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In this context and also as a part of our quest for new nickel(II) antimicrobials, [6] we were attracted towards synthesizing novel complexes where ligand framework may have the ability to exhibit redox non‐innocent property upon coordination. It has been well documented that the ligand frameworks with pyridyl/ benzothiazolyl moieties have the potential for antimicrobial activities [7] .…”
Section: Introductionmentioning
confidence: 99%
“…[4] It has also been found that certain complexes of nickel(II) can exhibit diverse in vitro biological activities, ranging from antimicrobial and antiinflammatory to antiproliferative as well as enzyme inhibitory and it has also been emphasized that complexes with redox-active ligands are probably responsible for the biological activities. [5] In this context and also as a part of our quest for new nickel(II) antimicrobials, [6] we were attracted towards synthesizing novel complexes where ligand framework may have the ability to exhibit redox non-innocent property upon coordination. It has been well documented that the ligand frameworks with pyridyl/ benzothiazolyl moieties have the potential for antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%